Pengaruh Penggunaan WhatsApp Terhadap Hasil Belajar IPA siswa kelas VA SDN Duri Kepa 03 Jakarta barat Pada Masa Pandemi. - Tri Lestari (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The study aims to see the effect of using WhatsApp on science learning outcomes at SDN Duri Kepa 03, using a survey method that distributes questionnaires via google form. The problem in this study is that students are required to use online learning methods at home and use their cellphones at all times, because most teachers send course materials and assignments through WhatsApp groups. The use of WhatsApp media also supports the elderly's economy, because at SDN Duri Kepa 03 most of them are from the lower middle class. In science learning, if you only rely on WhatsApp both in the process and the results are not optimal, because in science learning it discusses natural phenomena and the surrounding environment. The results of the partial test obtained tcount = 9.402 > ttable = 2.042. The result is H1 is accepted, which means that there is an influence with a coefficient of determination of 74.7%, the remaining 25.3% is influenced by other factors.